Role of Calcitonin Gene-Related Peptide in Nociceptive Modulationin Anterior Cingulate Cortex of Naïve Rats and Rats With Inflammatory Pain - Hou, Ke-Sai; Wang, Lin-Lin; Wang, Hong-Bo; Fu, Feng-Hua; Yu, Long-Chuan (Frontiers in Pharmacology, 2020)
As it is known that calcitonin gene-related peptide (CGRP) plays a key role in pain modulation in the brain. There are high expressions of CGRP and CGRP receptor in anterior cingulate cortex (ACC), an important brain structure in pain modulation. The present study explored the role and mechanisms of CGRP and CGRP receptor in nociceptive modulation in ACC in naïve rats and inflammatory rats. Administration of different does of CGRP in ACC induced significant antinociception in a dose-dependent manner in both naïve rats and rats with inflammatory pain. The CGRP-induced antinociception was attenuated by injection of the CGRP receptor antagonist CGRP8-37 in ACC. Interestingly, both CGRP-induced antinociception and CGRP receptor expression decreased in ACC in rats with inflammatory pain compared with naïve rats. Knockdown of CGRP receptor in ACC by siRNA targeting to CGRP receptor attenuated both the CGRP receptor expression and the CGRP-induced antinociception significantly in rats. These findings demonstrate that CGRP and CGRP receptor participate in nociceptive modulation in ACC in rats, inhibiting CGRP receptor expression induces decrease in CGRP-induced antinociception in ACC.